UNDANG – UNDANG PERLINDUNGAN ANAK TERHADAP KEKERASAN (KASUS : SEORANG IBU MEMBUNUH ANAK KANDUNG DI BALIKPAPAN) - Isnawati Isnawati (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
This aim of this research is to know the role of the regulation of the kids towards the unsuitable treatment.The location of the research is in Samarinda .The method of it is qualiative and library one .It takes three months by taking news from the local daily newspaper  , KaltimPost.The results of the research are (1). The name of the child is Johan Rafli Sultansyah Yusuf (13 years old), (2). He is very naughty  (3). He is a member of motorcycle gang which makes many trouble in West Balikpapan, (4). He is a trouble maker towards the female, (5). He is lazy to go o school (6). His mother is lost of control  she is, therefore, kills his son, (6). The people there are not gving her to see the burrial of her son. The suggestions are (1). A child must be controlled by his or her parents, (2). The parents must be patients, (3). The parents must be full of love towards the chiildren, (4). The parents must care of their chidren’s friends.